PENGARUH VARIABEL MAKROEKONOMI DI PASAR SAHAM: BUKTI DARI BURSA EFEK INDONESIA (BEI) PERIODE 2006-2015 - Maria Brenda Christie; Khairunnisa _; Vaya Juliana Dillak (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2017)
The world economic conditions which have been entered the era of globalization make a big influence of capital movement into financial market in emerging country, including Indonesia. Nowadays, almost all countries paying attention to the capital market because it has a major role in the economic development of a country. Seeing the development of the Indonesian capital market, one of the indicators used in assessing the market in general or measure whether the share price increase or decrease is the Composite Stock Price Index. This study examines the causal relationship between Composite Price Index in Indonesia Stock exchange with independent variable Inflation, SBI Interest Rate, and Gross Domestic Product (GDP). The period of this study is from 2006 to 2015. To meet the objectives of this study, the hypothesis is test using Granger Causality Test. The sampling method is using non probability sampling with saturated sample. This study uses secondary data from the annual report of Indonesia Stock Exchange, the annual report of Bank Indonesia, and Statistic Indonesian’s report.The result shows that there is bidirectional causality relationship between SBI Interest Rate variable with Composite Stock Price Index, while the variable of inflation and GDP does not have a causal relationship each other. In addition, this study shows that the variable of Inflation, SBI Interest Rate, and GDP simultaneous effect on Composite Stock Price Index in the Indonesia Stock Exchange on period 2006-2015. Keywords: Inflation, SBI Interest Rate, GDP, Composite Stock Price Index, Granger Causality